Assessment of nematicidal and plant growth-promoting effects of Burkholderia sp. JB-2 in root-knot nematode-infested soil - Kim, Jong-Hoon; Lee, Byeong-Min; Kang, Min-Kyoung; Park, Dong-Jin; Choi, In-Soo; Park, Ho-Yong; Lim, Chi-Hwan; Son, Kwang-Hee (Frontiers in Plant Science, 2023)
Root-knot nematodes (RKN), Meloidogyne spp., are plant-parasitic nematodes that are responsible for considerable economic losses worldwide, because of the damage they cause to numerous plant species and the inadequate biological agents available to combat them. Therefore, developing novel and eco-friendly nematicides is necessary. In the present study, Burkholderia sp. JB-2, isolated from RKN-infested rhizosphere soil in South Korea, was evaluated to determine its nematicidal and plant growth-promoting effects under in vitro and in vivo conditions. Cell-free filtrates of the JB-2 strain showed high levels of nematicidal activity against second-stage juveniles (J2) of M. incognita, with 87.5% mortality following two days of treatment. In addition, the assessment of the activity against 2 other six plant parasitic nematodes (M. javanica, M. hapla, M. arenaria, Ditylenchus destructor, Aphelenchoides subtenuis, and Heterodera trifolii) showed that the cell-free filtrates have a broad nematicidal spectrum. The three defense-responsive (MiMIF-2, MiDaf16-like1, and MiSkn1-like1) genes were activated, while Mi-cm-3 was downregulated when treated with cell-free filtrates of JB-2 cultures on J2. The greenhouse experiments suggested that the cell-free filtrates of the JB-2 strain efficiently controlled the nematode population in soil and egg mass formations of M. incognita in tomato (Solanum lycopersicum L., cv. Rutgers). An improvement in the host plant growth was observed, in which the shoot length and fresh weights of shoots and roots increased. The treatment with 10% of JB-2 cell-free filtrates significantly upregulated the expression levels of plant defenses (SlPR1, SlPR5, and SlPAL) and growth-promoting (ACO1, Exp18, and SlIAA1) genes compared with the corresponding parameters of the control group. Therefore, JB-2 could be a promising candidate for the sustainable management of RKN.